2008
DOI: 10.2170/physiolsci.rp010508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture Stimulation of Hindlimb on Seizure Incidence and Supragranular Mossy Fiber Sprouting in a Rat Model of Epilepsy

Abstract: Abstract:Recently, electroacupuncture (EA) has been gaining more and more attention as a treatment for epilepsy. However, concrete evidence is needed to better understand its antiepileptic effect and the mechanism underlying this effect. The present study was designed to assess the effect of EA stimulation of hindlimb on the incidence of behavioral seizures (spontaneous recurrent seizures, [SRS]) and electroencephalogram (EEG) seizures, and the extent of supragranular mossy fiber sprouting (MFS) using the lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previous studies suggested that acupuncture acted as a neuromodulating input into the CNS [43]. Recent research showed that acupunctural signal could travel to the CNS via afferent nerve pathways and cause various neurological and physiological changes [44]. For example, Choi et al .…”
Section: The Neuroprotective Effects Of Acupuncture In Brain Functionmentioning
confidence: 99%
“…Previous studies suggested that acupuncture acted as a neuromodulating input into the CNS [43]. Recent research showed that acupunctural signal could travel to the CNS via afferent nerve pathways and cause various neurological and physiological changes [44]. For example, Choi et al .…”
Section: The Neuroprotective Effects Of Acupuncture In Brain Functionmentioning
confidence: 99%
“…[60][61][62][63][64][65] In pre-clinical studies, pulsed ultrasound accelerated recovery after nerve injury, which suggests a potential clinical role for ultrasound after nerve injury. Adverse clinical outcomes have not been reported.…”
Section: Research Evidence Lowmentioning
confidence: 99%
“…60,61 In contrast, research using an animal model of epilepsy suggests that A-TENS applied to a limb may help reduce epileptic activity. 62 …”
Section: Research Evidence Moderatementioning
confidence: 99%
“…Therefore, we assert that applying 2 Hz EA at the ear can ameliorate mossy fiber sprouting of the hippocampus via multiple pathways and that the auricular-vagal afferent pathway plays a critical role. EA at ST36 can reduce the occurrence of epileptic seizure and supragranular mossy fiber sprouting in a lithium-pilocarpine-induced epileptic seizure rat model [14]; moreover, EA was thought to inhibit seizure via a hypothalamic arcuate nucleus and then through the brain stem to the hippocampus. We hypothesized that ST36-ST37 locate to the anterior tibial muscle could be innervated by a deep peroneal nerve, and the needles were inserted into the subcutaneous region in the SG and innervated by the superficial peroneal nerve.…”
Section: Discussionmentioning
confidence: 99%